Pengaruh Penambahan Bayam Hijau (Amaranthus Hybridus L) dengan Konsentrasi yang Berbeda terhadap Kualitas Bakso Ayam - Dinda Hutami Nono; Gomera Bouk; I Putu Juli Sukariada (Jurnal Multidisiplin Indonesia, 2026)
This study aims to analyze the effect of adding green spinach (Amaranthus hybridus L.) with different concentrations on the physical and chemical quality of chicken meatballs and to determine the best concentration that produces optimal quality chicken meatballs. The study used an experimental method with four treatments, namely P0 (0% spinach), P1 (5% spinach), P2 (10% spinach), and P3 (15% spinach). The parameters observed included crude protein, crude fat, water holding capacity, and tenderness. The test data were analyzed descriptively. The results showed that the addition of green spinach improved the quality of chicken meatballs. The crude protein content increased from 8.067% in P0 to 9.276% in P3. Conversely, the crude fat content decreased from 1.506% in P0 to 1.021% in P3. The highest water holding capacity value was obtained in treatment P2 at 35.671%, while the lowest value was found in P0 at 32.990%. The tenderness test showed the highest value in P3, namely 0.209 K/cm², which indicates that the meatball texture is more chewy, dense, and compact compared to other treatments. Based on the results of the study, it can be concluded that the addition of green spinach affects the physical and chemical quality of chicken meatballs. The best treatment was the addition of green spinach as much as 15% (P3) because it produced the highest protein content, lowest fat content, and the best level of tenderness, while the best water binding capacity was obtained in the 10% treatment (P2).